Love, sex, and commitment: relationship choices and trajectories among unmarried youth in India. Issue 2 (1st January 2022) - Darak, Shrinivas; Parchure, Ritu; Darak, Trupti; Kulkarni, Vinay
Abstract: There is limited research in India to understand young people's decision-making processes about intimate relationships before marriage. This paper, adopting a life course perspective, explains relationship choices and diachronic trajectories of relationships from adolescence to young adulthood. Retrospective data were collected from 1240 never married 20–29-year-old men and women living in Pune using a relationships history calendar. All the relationships from 10 years of age onwards were plotted on the calendar, and information on predictor variables was collected through structured questionnaires. Data were analysed using descriptive statistics. Sequence analysis approach was used to identify different typologies. Overall, 76% of the participants reported having at least one relationship. More women compared to men (84% vs 70%) ever had a relationship. The median age of starting the first relationship was 17 years for women and 18 for men. Different relationship types were reported, such as "serious", casual, "friends with benefit", and "exploring". The level of emotional involvement, commitment, and physical intimacy significantly differed in different relationship types with significant gender differences. Four typologies of relationships were observed, labelled as (1) Commitment–No sex ( N = 187); (2) Commitment–Sex-Some exploration ( N = 189); (3) No commitment–Exploration ( N = 281), and (4) No relationship ( N = 583). Compared to men, women were more likely to follow the trajectory of "Commitment-No sex" (RR 2.13, CI 1.5–3.03). Family environment was significantly related to young people's relationship choices. The findings strongly suggest the need to adopt a developmental perspective towards intimate relationships to understand and address the vulnerabilities of young people across the life course.